Integration of Electric Vehicle Charging Stations into the Electricity Grid: Karabük University Campus Case Study Using PDF, LHS and ANN - Altınkaya, Hüseyin (Fırat University, 2025)
The proportion of electric vehicles (EVs) within the total number of vehicles is increasing at an accelerating pace both in our country and globally. In this context, studies on the impacts of electric vehicles and charging stations on electrical grids, how much additional load they will place on the grids, and whether the existing electrical infrastructure will be sufficient for electric vehicles and charging stations in the short, medium, and long term are gaining importance. In this study, three different case studies were conducted at Karabük University Demir Çelik (central) Campus for the years 2025, 2030 and 2040. Case studies based on TOGG (Turkey’s Automobile Venture Group) brand electric vehicle parameters for Karabük University Demir Çelik campus electricity distribution network were examined. In order to estimate how much additional load electric vehicle charging stations (EVCS) will add to the grid, the Weibull distribution probability density function (PDF), latin hypercube sampling (LHS) approaches, and artificial neural networks (ANN) were used. The simulations of the obtained results were carried out using the ETAP Electrical Power System Analysis interface. It has been preicted that how many and what type of electric vehicle charging stations could be connected to the network within the campus according to 2025, 2030 and 2040 scenarios, and how much additional load the increase in the number of these stations will load the existing grid and whether additional investments are required.

Elektrikli araçların (EA) toplam araç sayısındaki oranı ülkemizde ve dünyada giderek yükselen bir ivmeyle artmaktadır. Elektrikli araçların ve şarj istasyonlarının elektrik şebekelerine olan etkileri, şebekelere ne kadar ilave yük getireceği ve mevcut elektrik şebekelerinin alt yapılarının elektrikli araçlar ve şarj istasyonları için kısa, orta ve uzun vadede yeterli olup olmadığı ile yapılan çalışmalar bu bağlamda önem kazanmaktadır. Bu çalışmada Karabük Üniversitesi Demir Çelik (merkez) yerleşkesinde 2025, 2030 ve 2040 yılları için üç farklı durum çalışması gerçekleştirilmiştir. Karabük Üniversitesi Demir Çelik kampüsü elektrik dağıtım şebekesi için TOGG (Türkiye’nin Otomobili Girişim Grubu) marka elektrikli araç parametreleri esas alınarak vaka çalışmaları yapılmıştır. Elektrikli araç şarj istasyonlarının (EAŞİ), şebekeye ne kadar ilave yük ekleyeceğini tahmin etmek için Weibull dağılımı olasılık yoğunluk fonksiyonu (OYF), latin hiperküp örnekleme (LHÖ) yaklaşımları ve yapay sinir ağı (YSA) kullanılmıştır. ETAP Electrical Power System Analysis arayüzü kullanılarak elde edilen sonuçların benzetimleri gerçekleştirilmiştir. Kampüs içindeki şebekeye 2025, 2030 ve 2040 senaryolarına göre kaç adet ve hangi tür elektrikli araç şarj istasyonunun bağlanabileceği ve bu istasyonların sayısının artmasının mevcut şebekeye ne kadar ek yük getireceği ve ilave yatırımlara gerek olup olmadığı öngörülmüştür.
Elektrikli Araç Şarj İstasyonlarının Elektrik Şebekesine Entegrasyonu: OYF, LHÖ ve YSA ile Karabük Üniversitesi Yerleşkesi Durum Çalışması
Keywords: Electrical Energy Transmission; Networks and Systems; Elektrik Enerjisi Taşıma; Şebeke ve Sistemleri; Power Plants; Elektrik Tesisleri